The role of NIV in chronic hypercapnic COPD following an acute exacerbation: the importance of patient selection?. (April 2016) - Duiverman, Marieke L.; Windisch, Wolfram; Storre, Jan H.; Wijkstra, Peter J.
Recently, clear benefits have been shown from long-term noninvasive ventilation (NIV) in stable chronic obstructive pulmonary disease (COPD) patients with chronic hypercapnic respiratory failure. In our opinion, these benefits are confirmed and nocturnal NIV using sufficiently high inspiratory pressures should be considered in COPD patients with chronic hypercapnic respiratory failure in stable disease, preferably combined with pulmonary rehabilitation. In contrast, clear benefits from (continuing) NIV at home after an exacerbation in patients who remain hypercapnic have not been shown. In this review we will discuss the results of five trials investigating the use of home nocturnal NIV in patients with prolonged hypercapnia after a COPD exacerbation with acute hypercapnic respiratory failure. Although some uncontrolled trials might have shown some benefits of this therapy, the largest randomized controlled trial did not show benefits in terms of hospital readmission or death. However, further studies are necessary to select the patients that optimally benefit, select the right moment to initiate home NIV, select the optimal ventilatory settings, and to choose optimal follow up programmes. Furthermore, there is insufficient knowledge about the optimal ventilatory settings in the post-exacerbation period. Finally, we are not well informed about exact reasons for readmission in patients on NIV, the course of the exacerbation and the treatment instituted. A careful follow up might probably be necessary to prevent deterioration on NIV early.